2012
DOI: 10.1002/jor.22150
|View full text |Cite
|
Sign up to set email alerts
|

Two‐week joint mobilization intervention improves self‐reported function, range of motion, and dynamic balance in those with chronic ankle instability

Abstract: ABSTRACT:We examined the effect of a 2-week anterior-to-posterior ankle joint mobilization intervention on weight-bearing dorsiflexion range of motion (ROM), dynamic balance, and self-reported function in subjects with chronic ankle instability (CAI). In this prospective cohort study, subjects received six Maitland Grade III anterior-to-posterior joint mobilization treatments over 2 weeks. Weightbearing dorsiflexion ROM, the anterior, posteromedial, and posterolateral reach directions of the Star Excursion Bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
154
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(182 citation statements)
references
References 36 publications
(67 reference statements)
19
154
2
7
Order By: Relevance
“…Left unaddressed, such components may contribute to longterm consequences associated with the condition. Although the exact cause of the reported deficits is unknown, previous investigators [36][37][38] have shown that various reha- bilitation techniques improve regional measures of function. Hence, regional measures of function appear to be modifiable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Left unaddressed, such components may contribute to longterm consequences associated with the condition. Although the exact cause of the reported deficits is unknown, previous investigators [36][37][38] have shown that various reha- bilitation techniques improve regional measures of function. Hence, regional measures of function appear to be modifiable.…”
Section: Discussionmentioning
confidence: 99%
“…The MDC indicates the amount of change required to exceed measurement variability, 39 whereas the MCID indicates the smallest difference that a patient perceives as a change in health status. 40 In individuals with CAI, MDC scores of 3.96% 36 and 7.9% 36 have been reported for the FAAM-ADL and FAAM-Sport, respectively. The median difference between groups in our study was 9% for the FAAM-ADL and 12% for the FAAM-Sport, indicating that these participants not only displayed significant differences compared with the healthy group but also had room for clinically meaningful improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Limited evidence is available regarding the reliability and MDC of the FAAM-S. Previously, an MDC of 15.5% was reported 19 in a college-aged population with chronic ankle instability. This MDC is higher than our MDC of 7%; we believe the difference could be attributed to injury history because we do not know if any of our participants had a history of chronic ankle instability.…”
Section: Test-retest Reliability and MDCmentioning
confidence: 99%
“…3) [83,84]. Hoch et al [82], showed improvements in range of motion with two weeks of grade 3 posterior talocrural mobilizations for three treatments of 5 min. Other interventions have included repositioning taping of the fibula to alter the joint structure but has not shown improvements in range of motion [85].…”
Section: Rehabilitationmentioning
confidence: 99%
“…These limit the posterior glide of the talus in the joint during dorsiflexion [15]. Joint mobilizations have been shown to improve dorsiflexion by improving the arthrokinematics of motion [82], and these differences have also been shown to carry over acutely to landing mechanics and in postural control (Fig. 3) [83,84].…”
Section: Rehabilitationmentioning
confidence: 99%